The Dutch Cone Penetration Test And Its Use In Determining The Pile Bearing Capacity - C. Van der Veen (Deep Foundations Institute, 1989)
The use of the quasi static (Dutch) Cone Penetration Test (CPT) is described as a tool to predetermine the ultimate bearing capacity of the pile point. An analysis is given why a purely theoritical approach does not meet with success. A practical method is explained of extrapolating the cone resistance to predict the pile point resistance. The method has been calibrated against the result of 32 selected high standard loading tests on pile points in the Netherlands.